Quantitative studies of gas porosity in cast aluminium & the determination of melt quality - Malisano, J (2018)
Gas porosity is one of the major defects that forms during solidification in cast aluminium alloys. Hydrogen, oxide films, and TiB2 based grain refiner are all known to play a role in the formation of gas porosity, however their individual influences are not fully understood, necessitating further investigation. In this work, metallography and low resolution X-Ray Computed Tomography (XCT), i.e. macro-CT, have been employed to study the effects of hydrogen, oxide films, and TiB2 grain refiner on the structure of porosity formed in Al-7Si samples that were cast using the Reduced Pressure Test (RPT). Porosity in the centres of castings that were solidified under atmospheric pressure is also examined using high resolution XCT, i.e. micro-CT. The studies of the structure of the porosity provided insight into the respective effects that the aforementioned factors play in the nucleation and growth of bubbles in the material during solidification. The results suggested that hydrogen provides the impetus for gas porosity formation, and the fuel for the expansion of the nucleated bubbles, while oxide films, and TiB2 grain refiner particles probably TiB2 clusters act as bubble nuclei, and provide a means for the hydrogen to come out of solution and form the bubble. The higher the oxide film content of a melt, the greater the fraction of hydrogen that may be released from solution. Another finding was that Premetz and PoDFA analysis proved unreliable for measuring the oxide film content of a melt; it was concluded that this due to their insensitivity to small oxide films. SEM microanalysis or the use of the RPT are therefore needed in order to measure melt oxide film content. The results provided new insight into the RPT and how it may be used as a measure of melt quality. In line with the current wisdom, the volume fraction of porosity was shown to indicate the combined hydrogen and oxide film content of the melt, while the pore number density was shown to be indicative of the oxide film content in the material.